Pengaruh Disiplin Kerja Dan Karakteristik Individu Terhadap Kinerja Karyawan PDAM Kabupaten Pasaman Barat - Jon M Maizar; May Yuliza; Endar Wita; Sintia Ramadhani (Universitas Hamzanwadi, 2022)
This research was conducted at PDAM (Local State Water Company) West Pasaman Regency. The purpose of this study was to determine the impact of Work Discipline and Individual Characteristics on Employees Performance at PDAM West Pasaman Regency. The population are all employees of PDAM West Pasaman Regency, amounting to 54 people. Because the population is below 100 people, sampling technique using is census method that is the entire population is sampled, so the number of samples are 54 people. The data collection methods used questionnaires and interviews. The data analysis method used descriptive analysis and multiple linear regression using SPSS 2016. The results of this study indicate a relationship between independent variable and dependent variable. It can be explained that (1) Work discipline has positive and significant impact on employee performance with regression coefficient of 3.896 and significant rate of 0.000 (0.05), (2) Individual characteristics has positive and insignificant impact on employee performance with regression coefficient of 1.225and significant rate of 0.226 ( 0.05), (3) The independent variables simultaneously have positive and significant impact on performance with regression coefficient value of 67.526 with significant rate of 0.000 (0.05). R2 value shows 72.6% and the remaining 27.4% is influenced by other variables which are not included in this study.